2011
DOI: 10.1128/jvi.02317-10
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Functional Relevance of a Transcription-Regulating Sequence Involved in Coronavirus Discontinuous RNA Synthesis

Abstract: Transmissible gastroenteritis coronavirus (TGEV) genomic RNA transcription generates 5-and 3-coterminal subgenomic mRNAs. This process involves a discontinuous step during the synthesis of minus-sense RNA that is modulated by transcription-regulating sequences located at the 3 end of the leader (TRS-L) and also preceding each viral gene (TRS-Bs). TRSs include a highly conserved core sequence (CS) (5-CUAAAC-3) and variable flanking sequences. It has been previously proposed that TRS-Bs act as attenuation or sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…1, nucleotides of the TRS-L core sequence and nucleotides adjacent to the TRS region were accessible to DMS modification, confirming that they are part of single-stranded regions. In conclusion, our structure model is consistent with previous betacoronavirus studies (Kang et al, 2006;Liu et al, 2007; and supports the idea that, in most coronaviruses, TRS-L is part of an unstructured region rather than a stable SL structure (Van Den Born et al, 2004;Dufour et al, 2011) (see also Discussion).…”
Section: Rna Structure Probing Analysis Of Alphacoronavirus 5'-terminsupporting
confidence: 91%
“…1, nucleotides of the TRS-L core sequence and nucleotides adjacent to the TRS region were accessible to DMS modification, confirming that they are part of single-stranded regions. In conclusion, our structure model is consistent with previous betacoronavirus studies (Kang et al, 2006;Liu et al, 2007; and supports the idea that, in most coronaviruses, TRS-L is part of an unstructured region rather than a stable SL structure (Van Den Born et al, 2004;Dufour et al, 2011) (see also Discussion).…”
Section: Rna Structure Probing Analysis Of Alphacoronavirus 5'-terminsupporting
confidence: 91%
“…Secondary structure analysis of the TRS-L region from transmissible gastroenteritis virus (TGEV) (23) and bovine coronavirus (BCoV) (24) showed that the CS-L is exposed in the loop of a structured hairpin that is relevant for replication and transcription (23). These observations provided experimental evidence for the selection of the TRS-L during the template switch, excluding other genome TRS-Bs that contain the CS.…”
Section: Coronavirus Replication and Transcriptionmentioning
confidence: 99%
“…Quantitative analysis of genomic RNA (gRNA) and subgenomic mRNAs (sgRNAs) from TGEV-derived replicons was performed by real-time RT-PCR using Bio-Rad iQ5 Real Time PCR System. The primers for qRT-PCR in this study were described in previous study (Dufour et al, 2011). Reactions were carried out in 25 l volume containing 1× SYBR Premix Ex TaqTM II (Takara, Dalian, China), sense and anti-sense primers and target cDNA.…”
Section: Rna Analysis By Real-time Rt-pcrmentioning
confidence: 99%